2020
DOI: 10.3390/ijerph17124611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Manual Therapy on Fatigue, Pain, and Psychological Aspects in Women with Fibromyalgia

Abstract: Fibromyalgia is a condition characterised by chronic widespread muscle pain and fatigue, sleep disturbances, cognitive disorders, and mood disturbance. The purpose of this study was to determine the effectiveness of a manual therapy technique performed with moderate digital pressure in women with fibromyalgia (n = 24). In this randomised, controlled trial, the participants were randomly assigned to the experimental group or placebo group. The experimental group was assisted with manual therapy sessions based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 60 publications
1
24
0
2
Order By: Relevance
“…This technique is used during intense exercise for muscle-soft tissue pain and fatigue. Previous evidence has found that massage has shown beneficial benefits by minimizing body tension and other DOMS side effects [7]. Other research [8] has also shown that FR is widely used during a period of physical exercise as a rehabilitation aid.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is used during intense exercise for muscle-soft tissue pain and fatigue. Previous evidence has found that massage has shown beneficial benefits by minimizing body tension and other DOMS side effects [7]. Other research [8] has also shown that FR is widely used during a period of physical exercise as a rehabilitation aid.…”
Section: Introductionmentioning
confidence: 99%
“…In compliance with these findings, some MT studies have strived to control the applied load, towards effect replicability, using approaches like patient pain feed-back scales, as for example includes the recently published work by Nadal-Nicolás et al [57]. Since pain sensitivity varies across FM patients, we thought that pressure monitorization performed by a single pre-trained collegiate physiotherapist might increase inter-assay consistency.…”
Section: Discussionmentioning
confidence: 88%
“…Fibromyalgia (FM) is a condition generally associated with multiple symptoms, such as sleep deprivation, tiredness, chronic fatigue and cognitive impairment [1,2]. Its predominant characteristic is non-articular, widespread, chronic muscular-skeletal pain in specific areas all over the body [3,4].…”
Section: Introductionmentioning
confidence: 99%